2014
DOI: 10.1111/ceo.12360
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse versus continuous wave transscleral diode cyclophotocoagulation in refractory glaucoma: a randomized exploratory study

Abstract: Diode transscleral cyclophotocoagulation in both micropulse and continuous modes was effective in lowering intraocular pressure. The micropulse mode provided a more consistent and predictable effect in lowering intraocular pressure with minimal ocular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
316
6
34

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(374 citation statements)
references
References 24 publications
18
316
6
34
Order By: Relevance
“…Recently, the micropulse diode laser [14] and UCP [8] have been introduced among others as novel techniques to partially destroy the ciliary body, with a more predictable and controlled IOP reduction as compared to traditional cyclodestructive procedures. Recent studies showed that UCP also induces the stimulation of the suprachoroidal and transscleral portions of the uveoscleral outflow pathway, thus allowing another additional hypotensive effect [7,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the micropulse diode laser [14] and UCP [8] have been introduced among others as novel techniques to partially destroy the ciliary body, with a more predictable and controlled IOP reduction as compared to traditional cyclodestructive procedures. Recent studies showed that UCP also induces the stimulation of the suprachoroidal and transscleral portions of the uveoscleral outflow pathway, thus allowing another additional hypotensive effect [7,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…At 18 months, significantly higher proportion of patients who received MP-TSCPC achieved successful outcome when compared to patients who received CW-CPC. There was no significant difference in retreatment rates and the ocular complication rate was significantly higher in eyes treated with CW-TSCPC [60].…”
Section: Micropulse Transscleral Cyclophotocoagulation (Mp-tscpc)mentioning
confidence: 71%
“…Aktuelle Fortschritte haben die Behandlungsoptionen bei refraktärem Glaukom um eine neue Methode erweitert: eine transsklerale Diodenlasertherapie für das Auge mit Mikropuls-Diodenlaser und Behandlung durch die Pars plana mit modifizierter Kontaktsonde [56,57]. Es wurde postuliert, dass die thermische Lokalisierung mit einem Mikropuls-Diodenlaser es ermöglicht, kollaterale Gewebeschäden gering zu halten und so die ausgeprägte Gewebezerstörung im Ziliarkörper, Epithel und in den Zilienfortsätzen zu vermeiden, die in histologischen Proben nach konventioneller transskleraler Zyklophotokoagulation (TSCPC) beobachtet worden ist [58].…”
Section: Therapieoptionenunclassified
“…Unter peribulbärer Anästhesie lässt sich der genannte Eingriff mit einer 810-nm-Infrarot-Diodenlaserstrahlung mit 2000 mW [56,57] im Mikropulsmodus (MP-TSCPC; IQ810 Laser Systems, IRIDEX, CA, Mountain View, USA) durchführen. Die Sonde ermöglicht die präzise Positionierung der Lichtleiterspitze 3 mm posterior des Limbus [56] entsprechend der Lokalisation der Pars plana.…”
Section: Therapieoptionenunclassified
See 1 more Smart Citation